Pengaruh Pendidikan Kewarganegaraan Terhadap Partisipasi Pemilih Pemula Pada Pemilihan Umum (Studi Kasus: Pemilu Gubernur Dan Wakil Gubernur Sumatera Utara Tahun 2018) - Helen NM Napitupulu; Ade Irma Sagala (Penerbit STKIP PGRI Bangkalan, 2019)
Simultaneous regional elections held in 2018 in 171 regions in Indonesia recorded voter reached73.24% of the total permanent voters list (DPT) available. There has been a decrease in the levelof community participation if compared to the 2017 elections which reached 74% (source: KPUData) become a matter of concern so that it does not continue to occur in every general election.One method used is through citizenship education. This study aims to determine whethercitizenship education for beginner voters can already be used as a basis in understanding andinterpreting the general election and is there a significant effect of citizenship education on theincrease in the participation of beginner voters in general elections. From the research conductedon 200 adolescent voters in 3 senior high schools and 2 universities in Medan took a case studyon the election of the Governor and Deputy Governor of North Sumatra in 2018. Final resultshowing that there was a strong correlation between citizenship education and the level ofparticipation of beginner voters in general election. when the citizenship education is receivedbetter by the beginner voters , then the level of participation in the election become higher.